Thesis Overview: Oscillating wave surge converters – Large eddy simulation modelling of wave farms hydrodynamics and its related energy potential - Guilherme Fuhrmeister Vargas; Alexandre Beluco (The Journal of Engineering and Exact Sciences)
The Oscillating Wave Surge Converter (OWSC) is one of the most relevant systems for harnessing energy from ocean waves, generating energy by capturing the horizontal component of wave motion. This technology, which is on a pre-commercial development scale, presents one of the greatest potentials for electricity generation, due to its operating principle and the great improvement in design experienced over the last few years. Today, Computational numerical modelling is one of the main tools for the study and design of this and several other power generation systems from sea waves. In this context, a detailed study of a wave farm composed of several OWSCs is necessary, which represents a case closer to reality, since most renewable systems include several modules of the same converter. Considering the complexity of the existing hydrodynamics in these cases, a numerical modeling methodology based on the Large Eddy Simulation (LES) methodology is applied to correctly represent the oscillation of the structure and the observed flow fields. In order to achieve the objectives, the OpenFOAM v.4.1 computational code and the OlaFlow extension are used, together with the Wall Adapting Local Eddy Viscosity (WALE) LES model, which allows a representation of the system very close to real application cases. The proposed model demonstrated a good adherence of the results when compared to experimental studies present in the literature. Likewise, it was observed that changes in wave height and period, bottom slope, wave reflection, spacing between converters, and the wave farm layout can cause important variations in the energy generated by the system, increasing or reducing considerably its efficiency, emphasizing the importance of these parameters in the design and development of this technology.